Kajian Etnobotani Tumbuhan Obat Hutan oleh Masyarakat Desa Pamoseang Kecamatan Mambi Kabupaten Mamasa - Rahman; Karim, Faradilah Farid; Irundu, Daud; Idris, Andi Irmayanti; Rusmidin; Ramli, Muhammad Agusfartham (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2025)
The Mamasa tribe living in Pamoseang Village still maintains the tradition of traditional medicine using plants from the forest. This study aims to determine what plants, plant parts, processing methods, and UV (Use Value) values of plants used as traditional medicine by the Pamoseang Village community, Mamasa Regency. Data collection in this study used observation, interview and documentation techniques. Data analysis techniques were carried out descriptively. The results showed that there were 18 types of forest plants used as traditional medicine, with the most frequently used part of the plant being the leaves (52%). The dominant method of use was by boiling them to drink (59%). The highest Use Value was possessed by the Chromolaena odorata plant at 1.33, indicating a high level of utilization in traditional medicine. Knowledge about medicinal plants is obtained from generation to generation and still persists strongly amidst limited access to modern health services. These results reflect the importance of the role of local wisdom in maintaining public health naturally and sustainably.